2016
DOI: 10.2147/copd.s103680
|View full text |Cite
|
Sign up to set email alerts
|

Smokers with emphysema and small airway disease on computed tomography have lower bone density

Abstract: Osteoporosis is more common in patients with COPD and in smokers. The aim of this study was to assess whether measures of emphysema and airway disease on computed tomography (CT) were associated with lower bone density or vertebral fractures in smokers with and without COPD. For this purpose, we included participants from the NELSON lung cancer screening trial. Bone density was measured as Hounsfield Units in the first lumbar vertebra, and vertebral fractures were assessed semiquantitatively. The 15th percenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Male smokers, with or without chronic obstructive pulmonary disease (COPD), had a significant risk of low CTBD and vertebral fractures 8 . CTBD was significantly lower in smokers with emphysema and small airway disease on CT 9 . Lower values of CTBD were also found in current smokers compared to former smokers 10 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Male smokers, with or without chronic obstructive pulmonary disease (COPD), had a significant risk of low CTBD and vertebral fractures 8 . CTBD was significantly lower in smokers with emphysema and small airway disease on CT 9 . Lower values of CTBD were also found in current smokers compared to former smokers 10 .…”
Section: Introductionmentioning
confidence: 78%
“…In many previous studies, CTBD has been shown to be an effective method of demonstrating bone mineral loss and has shown good correlation with DEXA-BMD 1,5,7,9,1116 . Recently, it was also reported that CTBD reflects bone mineral loss more sensitively than DEXA, although CTBD measures were calibrated using specific formulas 12 .…”
Section: Discussionmentioning
confidence: 97%
“… 35 Interestingly, the fundamental basis of emphysema is loss of lung tissue and recent data from the literature shows that emphysema is often associated with less tissue in other body compartments such as BMI, muscle wasting measured as a lower fat-free mass index (FFMI) 36 , 37 as well as low BMD. 6 , 7 , 10 Likewise, a recent study shows that at baseline, patients with more severe emphysema had lower BMI, lower FFMI and a higher prevalence of self-reported osteoporosis. 38 The results of our study are in accordance with this groundswell of literature and support the hypothesis of tissue wasting associated with those smokers that developed emphysema.…”
Section: Discussionmentioning
confidence: 98%
“…These findings were later replicated in other studies. 10,11 However, none of these studies have explored the association of different emphysema subtypes (centrilobular, panlobular and paraseptal) and the presence of low BMD. Centrilobular emphysema (CLE) is associated with a higher smoking history, 12,13 a unique systemic chronic inflammation 12 and a protease-antiprotease misbalance, 14 that is also associated with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the prevalence of either low BMD using gold standard DXA assessments or osteoporotic fractures in smokers with lung disease rarely include detailed assessments of lung function or radiographic emphysema (4,5). Those cohorts that aim to carefully phenotype smokers through pulmonary function testing and chest CT imaging often do not use gold standard assessments of BMD to define osteopenia or osteoporosis (11,(24)(25)(26), but rather rely on patient-reported osteoporosis or nonstandard BMD assessments. Unlike these studies, we combine gold standard DXA assessments of BMD with detailed physiologic and radiographic data in our longitudinal, albeit smaller, smoking cohort.…”
Section: Original Researchmentioning
confidence: 99%